Falsafah al-Kindi Tentang Akal: Analisis Awalan dan Terjemahan Risalah Fi al-'Aql - Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
This article is basically an effort to give a preliminary analysis on al-Kindi's view on intellect based on his Risalah fi al-'Aql. The main purpose of the article is to provide Malay readers an annotated translation of one of the most important treatise on intellect in the history of Islamic Philosophy written by al-Kindi (185 A.H/801 C.E), the philosopher of the Arabs.